Beyond police boundaries: network analysis of multi-jurisdictional crime - A. M. Fox; M. Ogaki; J. C. Pickering (Russian Journal of Economics and Law)
Objective: network analysis of multi-jurisdictional crime in the United States of America.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors, which predetermined the following research methods: formal-logical, comparative-legal, and sociological. Results: in spite of the long-standing belief that crime is not restricted by arbitrary city or law enforcement jurisdictional boundaries, with a few exceptions, previous network studies relying on law enforcement data have been limited to criminal networks in one jurisdiction. Using incident and arrest data from seven law enforcement agencies in King County, Washington, the current study constructed crime specific multi-jurisdictional co-offending networks for four categories of crime: 1) violent, 2) property, 3) sex, and 4) domestic violence. Results indicate the existence of highly socially connected criminal networks in the county, with a higher percentage of offenders committing violent and property crime in two or more jurisdictions (16.8 and 29% respectively). Moreover, logistic regression models indicate that network position of an individual is a significant predictor of engaging in multi- jurisdictional offending. For violent crime, offenders with high betweenness centrality are likely to operate multi-jurisdictionally. Scientific novelty: the findings support the existence of a sizeable portion of offenders that cross jurisdictional boundaries to commit crime, implying the importance of sharing data among law enforcement jurisdictions.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activities when considering issues related to the crime prevention and suppression.